Multi-version to ensure the confidentiality and integrity of information: models and methods - Харченко, В. С.; Халин, М. Б. (Problems of Informatization and Control, 2004)
Possibility of application of a principle of multiversion principle for support of confidentiality and information integrity is parsed. The theoretical analysis of a diverse hashing functions is made out